THE ICJ’S ADVISORY OPINION ON CLIMATE CHANGE: A POSITIVE, YET SMALL, STEP FORWARD - Maurer, Melanie (Pravni zapisi, 2025)
The ICJ’s Advisory Opinion on the obligations of States in respect of climate change represents a pivotal moment in international environmental law. Being one of three recent decisions on this matter, the Opinion fits neatly within a growing body of jurisprudence aimed at compelling States to fulfill their internationally owed duties. The Opinion clarifies that States have legal obligations from a panoply of legal instruments to mitigate, adapt and cooperate in regard to the adverse effects of climate change. A breach of these obligations constitutes an internationally wrongful act and triggers State responsibility. Additionally, the Court endorsed the 1.5°C temperature goal as a legally binding target. While the Opinion is laudable in many respects, others could have been improved. These include the reluctance of the Court to give a definite answer on the rights of future generations and the question of continued statehood due to the permanent loss of territory due rising sea levels.